2008
DOI: 10.1111/j.1753-6405.2008.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

The seasonality in heart failure deaths and total cardiovascular deaths

Abstract: Objectives: To examine the seasonal pattern in heart failure (HF) and cardiovascular disease (CVD) by climate and cause of death in Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 25 publications
3
49
1
6
Order By: Relevance
“…A study in Australia found a 23% increased risk of death from heart failure in winter. Because winter in Australia is mild, this finding strongly implicates lower serum 25(OH)D levels rather than low winter temperatures [450].…”
Section: 24mentioning
confidence: 90%
See 1 more Smart Citation
“…A study in Australia found a 23% increased risk of death from heart failure in winter. Because winter in Australia is mild, this finding strongly implicates lower serum 25(OH)D levels rather than low winter temperatures [450].…”
Section: 24mentioning
confidence: 90%
“…Evidence exists that the seasonality of CVD is linked to solar UVB [447]. However, the effect of colder temperatures in winter cannot be completely ruled out as an explanation for the observed seasonality [448,449], although probably not as important as vitamin D, on the basis of findings regarding seasonality of CVD deaths in warm countries such as Australia [450].…”
Section: Cardiovascular Diseasementioning
confidence: 95%
“…Estudo com dados da Austrália avaliou a variação sazonal na mortalidade para sete grupos de doenças cardiovasculares. O maior aumento durante o inverno ocorreu para o grupo de insuficiência cardíaca (Barnett et al, 2008). O mesmo padrão com maior incidência de mortes por insuficiência cardíaca no inverno foi relatada na Argentina (Diaz et al, 2007).…”
Section: Insuficiência Cardíacaunclassified
“…Uma meta-análise avaliou o excesso de mortalidade cardiovascular nas segundas-feiras, o resultado foi uma odds ratio de 1,19 (IC 95%: 1,17-1,21) sendo um pouco maior para o sexo masculino (Witte et al, 2005). Outra meta-análise avaliou o excesso de morbidade de eventos cardiovasculares, confirmou um pequeno excesso nas segundas-feiras (Barnett et al, 2008). No caso da cidade de São Paulo, os dados do presente estudo condizem com a literatura, ou seja, foi identificado um pico nas segundasfeiras e esse padrão foi bem claro para o sexo masculino.…”
Section: Natal Ano Novo E Demais Efeméridesunclassified
See 1 more Smart Citation